Acute compartment syndrome due to delayed tourniquet release in distal forearm osteosynthesis: A case report - Tuan Mohd Ridzuan, Tuan Hussin; Mohd Anuar Ramdhan, Ibrahim; Faris Indra Prahasta, Didi Indra (2022)
Compartment syndrome is a known complication in trauma. Commonly it occurs immediately after trauma and involves lower limbs especially in tibial fractures. However, it can also happen after internal fixation and less commonly in upper limb fractures post-surgery. This is a case of compartment syndrome of the forearm developed after open reduction and plating of distal shaft of radius and ulna secondary to hematoma collection. The use of tourniquet intra-operatively that was deflated after skin closure masked the bleeding from small arteries. Fasciotomy performed and plate was left in situ without subsequent major complication